2014
DOI: 10.1097/iop.0b013e3182a74e55
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Ganglioneuroma in a Patient With Orbitopalpebral Neurofibromatosis

Abstract: Ganglioneuroma is a rare, benign tumor originating from the sympathetic ganglion cells. Choroidal ganglioneuroma in association with neurofibromatosis type 1 (NF-1) has been reported in a few cases. This study describes a 21-year-old woman with orbitopalpebral NF, who underwent evisceration for pseudophakic bullous keratopathy, intractable glaucoma, and absolute painful eyes and who was found to have choroidal ganglioneuroma and retrobulbar plexiform neurofibroma on histologic examination. This case, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…They may be associated with multiple endocrine neoplasia type IIB and NF1. Since the first reported case of a choroidal neurofibroma containing ganglion cells in 1925, only a handful of cases have been discussed in the literature . Exceptionally, ganglion cells are also found in the ciliary body .…”
Section: Discussionmentioning
confidence: 99%
“…They may be associated with multiple endocrine neoplasia type IIB and NF1. Since the first reported case of a choroidal neurofibroma containing ganglion cells in 1925, only a handful of cases have been discussed in the literature . Exceptionally, ganglion cells are also found in the ciliary body .…”
Section: Discussionmentioning
confidence: 99%
“…Reports on choroidal GN with NF1 have been scarce in the literature, with a PubMed search retrieving only 6 published case reports [5,6,7,8,9,10]. In all cases, the GN was not suspected clinically.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors can present with buphthalmos, intractable glaucoma, or as a blind, painful eye [1,2,3,4,5,6,7,8,9,10]. On review of the literature, we found only 9 prior cases of uveal ganglioneuroma reported [1,2,3,4,5,6,7,8,9,10], 7 of which were in the setting of newly diagnosed or previously established NF1 [1,2,3,4,5,6,7,8]. One case of choroidal ganglioneuroma without confirmed NF1 has been reported in the German literature [9], and 1 case was reported in the French literature of which details were not accessible [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioneuroma of the choroid is a rare tumor usually associated with neurofibromatosis type 1 (NF1), with only 9 cases previously reported [1,2,3,4,5,6,7,8,9,10]. Cowden syndrome is caused by a germline mutation in the PTEN tumor suppressor gene and is characterized by hamartomatous growths as well as an increased risk for breast, thyroid, endometrial, renal, and gastrointestinal cancer [11].…”
Section: Introductionmentioning
confidence: 99%